La participación de las organizaciones de la sociedad civil en la Cooperación Sur-Sur de Brasil: buscando un enfoque integral de participación - Michele DOlCETTI MARCOLINI (Revista Iberoamericana de Estudios de Desarrollo, 2014)
Dynamics of South-South (SSC) and Triangular Cooperation provided challenging interpretations and gained an autonomous space in the agendas of development and international cooperation’s research. Recently, we observed the emergence of critical contributions from civil society, trying to impact the development cooperation of southern countries. Civil Society Organizations (CSOs) suggest alternative principles and practices, re-appropriating their interpretations about participation, which were traditionally elaborated from northern CSOs. Nowadays, there are no structured studies describing this dynamics. This article, through the experience of civil society articulations in Brazilian SSC, tries to propitiate this research, encouraging the formulation of alternative action frames and the rise of interpretations from the South. To do so, we analyze how Brazilian CSOs try to enhance their role in formulation, implementation and accountability of Brazilian SSC. We conclude emphasizing the importance of an integral and challenging approach, allow to understand the multiple interrelations among State and Civil Society